Evaluation of Progressive Retinal Degeneration in Bipolar Disorder Patients over a Period of 5 Years. (3rd July 2022) - Satue, Maria; Fuentes, Juan Luis; Vilades, Elisa; Orduna, Elvira; Vicente, Maria Jose; Cordon, Beatriz; Perez-Velilla, Javier; Garcia-Campayo, Javier; Garcia-Martin, Elena
Abstract: Purpose: To quantify visual and retinal changes in patients with bipolar disorder (BD) over 5 years, compared with controls. Methods: Thirty-eight patients with BD and 122 healthy subjects underwent visual acuity (VA) evaluation, contrast sensitivity vision testing (CSV) with the Pelli Robson and CSV 1000E tests, and retinal thicknesses measurement [ganglion cell layer (GCL) and retinal nerve fiber layer (RNFL)] using Spectralis Optical Coherence Tomography (OCT). All subjects were re-evaluated after 5 years. The relationship between progressive structural changes and disease duration was analyzed. Results: Visual function parameters in BD patients remained unchanged during the follow-up period. A progressive decrease affecting macular and peripapillary RNFL thickness ( p < 0.050) was observed in patients. Progressive changes in BD were more pronounced when compared with healthy controls ( p < 0.050). A significant correlation between GCL thickness changes and disease duration was found (GCL outer temporal, r = −0.680, p = 0.016; GCL central, r = −0.540, p = 0.038). Conclusions: Progressive axonal loss was detected in BD patients. Visual function parameters were not affected after the 5-year follow-up. Despite observed changes in the neuroretina of patients with BD, axonal degeneration in these patients seemed to be mild and might be slowed down by other factors, such as BD treatments.